AJEN KAAGAMAAN DINA CARITA PANTUN RADEN PAMANAH RASA PINTONAN JURU PANTUN AYI RUHYAT (ulikan struktural jeung semiotik) - Kusmayadi Permana, - (2022)
The background in this study is to describe the carita pantun Raden Pamanah Rasa show of juru pantun Ayi Ruhyat. This research aims to find out: 1) the description of carita pantun Raden Pamanah show of juru pantun Ayi Ruhyat; 2) religious values in the search for carita pantun Raden Pamanah Rasa; 3) structural elements (story facts, themes, and story facilities) that exist in the carita pantun Raden Pamanah Rasa; 4) semiotic elements (icons, indexes, and symbols) that are on the offering of carita pantun Raden Pamanah Rasa. The method used is a descriptive method with a qualitative approach. The techniques used are observation, interview, and documentation. Research data sources consist of people (people), places (places), and paper (paper). The results of the research obtained are the religious value that exists in the carita pantun Raden Pamanah Rasa show of juru pantun Ayi Ruhyat, which is the science of fiqih. Structural elements (story facts, themes, and story facilities) that exist in the carita pantun Raden Pamanah Rasa is; 1) The theme of this guided carita pantun discusses religion, 2) the flow used by the author in this guided carita pantun is an advanced groove or conventional groove, 3) the character or characterization in this carita pantun is 7, 2 main characters and 5 additional figures, 4) the background in this carita pantun is 9 place settings and 5 time settings, 5) the title on this story is "Raden Pamanah Rasa" this title is in accordance with the main character told by juru pantun, 6) the point of view used in this carita pantun is the first person's point of view, 7) the style of language used by the author in this carita pantun more uses the style of parable language. Semiotic elements in the offering of carita pantun Raden Pamanah Rasa is 1 icon, 1 index, and 25 symbols. The conclusion of this study is expected to increase knowledge about carita pantun and carita pantun art, one of which is the art of carita pantun presented by juru pantun Ayi Ruhyat in Subang regency.